(untitled) (Proceedings OPTIMAL, 2025)
Background: Stroke is the death of brain tissue (cerebral infarction) which occurs due to reduced blood and oxygen flow to the brain. In stroke patients, the main problem that arises is disability, namely paralysis in the limbs, such as in the fingers, which causes a decrease in muscle strength. One effort that can be made to improve motor function of the extremities is rubber ball grip therapy. Purpose: The aim of this case study is to describe the application of rubber ball grip therapy in increasing upper extremity muscle strength in non-hemorrhagic stroke patients in a family context. Method: This research design uses a descriptive method with a case study approach (case study research). This ball grip therapy method is carried out for 7 consecutive days in the morning, afternoon and evening for 30 minutes. Data collection methods use interview techniques, physical examination, observation, and literature study. Results: The participants in this case study are Mrs. S’s family, one of whose family members suffered from a stroke with nursing problems involving impaired physical mobility. After being given rubber ball grip therapy intervention for 7 days, it was proven that muscle strength increased from 3 to 4 on the seventh day. Conclusion: It was found that the application of rubber ball grip therapy can increase muscle strength. Suggestions for families to continue implementing the therapy that has been taught regularly and regularly to increase muscle strength.